Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.18203/2320-6012.ijrms20185388
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity and mortality profile of neonates admitted in special newborn care unit of a teaching hospital in Uttarakhand, India

Abstract: Background: India accounts for 24% of global neonatal mortality. It is important to study the mortality and morbidity pattern as it helps to implement new treatment protocols, interventions, planning and policy making which helps in better survival and improvement in the quality of life among survivors. The aim of the project study was to determine the causes of morbidity and mortality in neonates admitted in our hospital.Methods: This study was conducted at Special Newborn Care Unit (SNCU) of Veer Chandra Sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
10
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 5 publications
(14 reference statements)
10
10
2
Order By: Relevance
“…NNH was found to be the most common indication for SNCU admission in the current study (25.99% of neonates). This finding is in line with the other studies by Adikane et al, Kumar et al,and Saharia et al [14,15,17]. However, in the study published by Verma et al, respiratory distress was reported as the most common indication for admission, whereas Panigrahy et al reported prematurity (39.2%) as the most common cause of admission [13,16].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…NNH was found to be the most common indication for SNCU admission in the current study (25.99% of neonates). This finding is in line with the other studies by Adikane et al, Kumar et al,and Saharia et al [14,15,17]. However, in the study published by Verma et al, respiratory distress was reported as the most common indication for admission, whereas Panigrahy et al reported prematurity (39.2%) as the most common cause of admission [13,16].…”
Section: Discussionsupporting
confidence: 87%
“…Jindal et al reported similar finding with 1.9% mortality, whereas majority of studies published from India reported higher mortality rate [21]. The previous studies have reported mortality rates ranging from 10.45% to 26% [9,13,15,16,18].…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…25 It is lower than the study done in MizanTepi, Ethiopia where mortality was (22.8%) 26 But it was higher than studies done in Ethiopia, at University of Gonder14.3%, Felege Hiwot referral hospital 13.29% and India 11.41%. 15,27,28 This high degree of variation in mortality rate could be due to the difference in the health facility setups because some of the setups could be well-equipped, the presence of skilled manpower, also the difference in methodology use and the study participants' economic status.…”
Section: Discussionmentioning
confidence: 99%